The return of the subject in the global economy. Recovering subjectivity in the face of consumer life, a proposal from the social economy (National Administration Journal, 2022)
The return of the subject is analyzed, it implies breaking with an alienated subjectivity given in modernity. The return of the subject begins when the categorical frameworks of mythical reason and instrumental reason collapse, and in doing so the subject knows, acts and positions itself to transform reality. In this context, the social economy, as a possible alternative for the articulation of social and political collectives, can influence an agenda to protect society and nature from the destruction carried out by human beings through imaginary economic models. The Charter of Principles of the Social Economy provides a path to follow, which places the person at the center, so that the social economy becomes a real possibility, in the search for a society in which everyone has a place.
Keywords: Mythical reason; instrumental reason; imaginary societies; irrationality